Managing Customers as Investments The Strategic Value of Customers in the Long Run - Gupta, Sunil; Lehmann, Donald (Pearson, 2005)
What's a customer really worth? Can you find out, without endlesslycomplex modeling? And once you know, what should you do with thatknowledge? Managing Your Customers as Investments has the answers.You'll learn simple ways to get reliable customer value information--ina form you can use. You'll discover how to use it to measure marketingeffectiveness, generate improvements throughout the entire customerrelationship lifecycle, and improve decision-making. Everyone tells youto manage your business around customers. This book gives you the toolsto do it.
Online resource; Title from title page (viewed January 19, 2005)
Keywords: Consumers; Consumers' preferences; Consommateurs; Préférences; Consommateurs; consumers